Factores de riesgo perinatales asociados al desarrollo de parálisis cerebral infantil en niños nacidos a término - Trujillo Montoya, Gladys Carolina (2017)
To analyze the relationship of perinatal risk factors in the study: Apgar ≤ 3 at 5 minutes, Placental Abruption and Clinic chorioamnionitis; associated with the development of Cerebral Palsy in born at term children. Material and methods: Case-control study comparing two groups: 57 children with cerebral palsy and 171 patients without this diagnosis. Comparison was made in both groups of risk factors: Apgar ≤ 3 at 5 minutes, Placental Abruption and Clinic chorioamnionitis; calculating the odds ratio for each risk factor and applying the chi-square statistical test. Results: Odds ratio and chi-square values for the risk factors under study are: Apgar ≤ 3 at 5 minutes: OR: 43.8, x2: (p <0.01); Placental abruption: OR: 1.5; X2: (p> 0.05); Clinic chorioamnionitis: OR: 7.6; X2: (p <0.01). Conclusions: Apgar ≤ 3 at 5 minutes and Clinic chorioamnionitis are risk factors for the development of Cerebral Palsy for Children. Placental abruption does not provide statistical significance to be a risk factor